1992
DOI: 10.1079/bjn19920086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ileo-rectal anastomosis and post-valve T-caecum cannulation on growing pigs

Abstract: The effects of post-valve T-caecum (PVTC) cannulation and end-to-side ileo-rectal anastomosis (IRA) on growth performance, nitrogen retention and intestinal fermentation were measured in growing pigs by comparison with a control group of intact animals. There were no differences between PVTC-pigs and intact pigs in growth performance and N balance. In IRA-animals reduced growth (P < OOl), less efficient feed conversion (P < 0.01) and decreased N retention (P < 0,001) were found. Indices of fermentation measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
(9 reference statements)
0
11
0
2
Order By: Relevance
“…Bartelt et al (1999) obtained DAPA / bacterial N ratios of 34.4 and 22.3 mg/g for miniature and domestic pigs with re-entrant ileo-caecal cannulae. Kö hler et al (1992) reported somewhat lower values for pigs with PVTC cannulae (13.9 to 16.7 mg/g) and ileo-rectal anastomosis (14.3 to 27.5 mg/g). In the study of Wü nsche et al (1991), the DAPA / bacterial N ratios were 7.5 to 18.8 mg/g for pigs with re-entrant ileo-caecal cannulae and 10 to 39.6 mg/g for pigs with ileo-rectal anastomoses.…”
Section: Figurementioning
confidence: 90%
“…Bartelt et al (1999) obtained DAPA / bacterial N ratios of 34.4 and 22.3 mg/g for miniature and domestic pigs with re-entrant ileo-caecal cannulae. Kö hler et al (1992) reported somewhat lower values for pigs with PVTC cannulae (13.9 to 16.7 mg/g) and ileo-rectal anastomosis (14.3 to 27.5 mg/g). In the study of Wü nsche et al (1991), the DAPA / bacterial N ratios were 7.5 to 18.8 mg/g for pigs with re-entrant ileo-caecal cannulae and 10 to 39.6 mg/g for pigs with ileo-rectal anastomoses.…”
Section: Figurementioning
confidence: 90%
“…Furthermore, studies that have examined the effect on the animal of long-term PVTC cannulation have concluded that the PVTC cannula does not significantly alter the metabolism of the pig and that the approach is therefore suitable for the collection of digesta. 12,13 It was expected, based on published conclusions by other workers, that the digesta collection method (PVTC cannulation) would allow a near complete quantitative collection of digesta over the 24 h collection periods. This did not occur, however, with an average marker recovery of only 72%.…”
Section: Discussionmentioning
confidence: 99%
“…The diets were mixed with water (1:1 w/v) immediately prior to feeding, and water was freely available between meals. The basal diet was gradually introduced over the following 4 days (days [11][12][13][14]. Each pig received the basal diet for 6 days before receiving the test diet.…”
Section: Diets and Feedingmentioning
confidence: 99%
“…Por outro lado, o conteúdo de sódio nas fezes foi maior nos animais do T3 que naqueles que receberam ração à vontade (P=0,07), o que é de difícil explicação, uma vez que a maior parte do sódio é excretada pela urina (Kohler et al, 1992), que não foi analisada. Entretanto, uma das funções do sódio é participar no transporte ativo secundário, na absorção de vários nutrientes no intestino (Vander et al, 1980).…”
Section: Resultsunclassified